Sustainability governing entities in higher education throughout Chile - Mac-Lean Bravo, Claudia Alejandra; Vargas, Luis Santiago; Uribe, Gonzalo; Aldea Venegas, Cristian Leonardo; Lares, Lorna; Mercado, Oscar (My University, 2021)
Purpose The purpose of this paper is to provide a panoramic and systematic view of 10 Sustainable Campus Network (SCN) universities' internal entities in charge of the sustainability effort - such as offices, committees, units, programs, or other, showing how some institutions have gained increasing deployment and momentum. However, their appearance and growth pathways have had significant disparities. Design/methodology/approach Global and local agendas have had a strong influence on Chilean higher education institutions. A relevant signal has been the creation of the SCN, formed by 21 Chilean universities, whose vision is to help shape a fair and environmentally healthy civilization contributing from the higher education realm. This work adopts a survey design methodological approach. It describes the following resulting components obtained from the aggregated data: (a) emergence processes and environments, (b) governance models and operational mechanisms, (c) networks and collaboration, and (d) final products generated, for sustainability governing entities within universities in Chile. Findings The main findings indicate that at the institutional level, the Cleaner Production Agreement for higher education institutions and the creation of the SCN have been key drivers in the formalization of several entities leading the sustainability efforts within Chilean universities. Also, regarding the degree of commitment to sustainability, the most active internal stakeholder corresponds to students. Originality/value The present work represents a pioneering effort in the Chilean context to identify and systematize the challenges, organizational structures, and key accomplishments of sustainability governing entities in higher education nationwide.
Keywords: university; governance; sustainability; higher education; sustainability office; sustainability governing entities